Turkish language researches in Mustafa Kemal Ataturk’s period - Kabadayi, O. (Journal of Oriental Studies, 2021)
Mustafa Kemal Ataturk was closely interested in Turkish history and Turkish language. He also gave great importance to Turkish culture in general manner. Furthermore, he attempted to improve and increase culture. He paid attention to language which carries culture and is an important element of culture. He tried to bring specific features as individualism and personality to Turkish language- the features that he aimed to bring to his nation in a republican country which were founded under the name of “Turk” and of which basic element was “culture”. However, reforms about language cannot be reached to the solution with only a few legislations and in a short time. Language studies are related to culture and requires quite a long time. Being aware of the fact that language is the basis of culture, Atatürk extended language studies over a period of time by taking some steps. The steps taken by Atatürk in order to improve and modernize Turkish language are the followings: founding of Institute of Turkic Studies, accepting of New Turkish Alphabet, founding of Turkish Language Investigation Association, organizing Turkish Language Congresses, Sun Language Theory, founding of Language and History-Geography Faculty, reproducing Turkish terms. Key words: Mustafa Kemal Atatürk, Turkish language, Turkish language reform.